EVALUATION OF EXPERIENTIAL MARKETING WEBSITE FOR ATTRACTING FOREIGN STUDENTS TO LATVIAN HIGHER EDUCATIONAL INSTITUTIONS - Sotikova, Natālija; Cāne, Renāte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Today experience marketing is attracting greater attention of researchers and practitioners, considering it an innovative approach to be used by companies and brands for development and retainment of their competitive advantage. This experience can develop online or as a result of offline activities. It is widely thought that many marketing instruments can be used in experiential marketing as long as they guarantee high engagement of consumers. The main instruments for sales promotion include mobile content and exclusive online content. Under the following topic, these can be special groups in social networks, mobile applications, websites of higher educational institutions etc. Unfortunately, there is a lack of research on consumer experience and its management in higher education, especially about education obtained abroad, as well as the usage of experiential marketing for attracting foreign students to Latvian higher educational institutions. These factors explain the importance and rationale of the chosen topic. The aim of the research is to evaluate the contents, availability and usage of foreign students’ interactive communication websites for attracting foreign students in Latvia in experiential marketing context. Method of research: content analysis of foreign students’ groups in social networks, websites and social network profiles of higher education institutions. In general, it can be concluded that the number of interactive online groups for foreign students in Latvia was insignificant, mainly the groups were inactive, the members of these groups provided negative comments or reacted openly to different publications. However, it is important to admit that personal publications received more “likes” and comments indicating the necessity of building a personal dialogue with students on websites.